And yet they help: An analytical model of how subsidies for modernizing landlords overcome inefficient tenancy law - Leo Florian Reutter; Georg Von Wangenheim (Philipps-University Marburg, School of Business and Economics, 2023)
In the rental residential building stock, the landlord-tenant-dilemma is a well-known barrier to investments in energy efficiency and exacerbated where rent control limits the possibility to raise rents to finance landlords' investments. Some jurisdictions, like Germany, allow landlords to extraordinarily increase rents in proportion to a modernization's costs. In addition, the government grants subsidies to home-owners investing in energy efficiency. However, landlords must deduct these subsidies from modernization costs that may be levied on tenants. In this paper we model the interaction of these two policies. We find that the modernization surcharge itself is inefficient regarding landlords' and tenants' welfare. Non-deductible subsidies help incentivizing otherwise unprofitable modernizations, thereby improving the modernization width at the cost of tenants' welfare, but at low levels they do not enlarge otherwise profitable modernizations. Deductible subsidies prove to be beneficial for landlords and achieve increases in landlords' optimal modernization extent, improving modernization depth. Deductible subsidies can still incentivize investment where none is profitable without, albeit less effectively. When large enough to overcome the inefficient incentives of the modernization surcharge, deductible subsidies can also guarantee both landlords and tenants to gain welfare as well as increasing overall Social Welfare.
Keywords: H23; K25; Q48; 330; energy efficiency; landlord-tenant-dilemma; residential building sector; subsidies; tenancy law